Satisfaction with online education among students, faculty, and parents before and after the COVID-19 outbreak: Evidence from a meta-analysis - Xu, Tianyuan; Xue, Ling (Frontiers in Psychology, 2023)
The outbreak of COVID-19 provided a historical opportunity for the arrival of the online education era, as billions of students across 190 nations have been compulsively required to attend online courses at home. The degree of satisfaction can be regarded as one of the major factors in determining the quality of online educational programs, hence many empirical studies have reported the rate of satisfaction with online education over the past two decades. However, few studies have integrated previous findings of the same research question. Therefore, to reinforce statistical power, the paper aims to conduct a meta-analysis for examining satisfaction with online education among students, faculty and parents before and after the COVID-19 outbreak. A total of 52 studies in English have been screened from 6 academic electronic databases, yielding 57 effect sizes via Comprehensive Meta-Analysis (CMA) software. The results showed that that the prevalence of satisfaction with online education among students, faculty and parents before and after the COVID-19 outbreak was 59.5%, 75.3% and 70.7% respectively, with a significant difference between satisfaction rate of students and that of their faculty and parents. Besides, moderator analysis found that: (1) Significantly more students in the context of the pre-pandemic era, not emergency online environment and developed countries were satisfied with online education than their counterparts in the post-pandemic era, emergency online environment and developing countries. Additionally, significantly more adult education learners were satisfied with online study than k-12 and university students. (2) Faculty in the non-emergency situation reported almost twice as great a satisfaction rate as their counterparts in the emergency circumstance. Facing less satisfied remote learning students, efforts could be made by giving well-designed online lessons via faculty and strengthening digital infrastructure via governments to improve students satisfaction.